Research trends of nanomaterials in Helicobacter pylori: a bibliometric analysis from 2003 to 2023 - Lei, Yeqing; Chen, Tao; Du, Qin; Yu, Weihua (Frontiers in Pharmacology, 2025)
BackgroundH. pylori infects approximately half of the global population and is associated with numerous diseases, posing a significant public health challenge. Recently, there has been increasing focus on researching nanomaterials for H. pylori. This study aims to visually evaluate the current status and trends of nanomaterials in H. pylori research by bibliometric analysis.MethodsH. pylori-related nanomaterials publications were retrieved from WoSCC and articles meeting the criteria were included in the analysis. The data was analyzed by Microsoft Excel, CiteSpace, and VOS viewer.ResultsThis bibliometric analysis included 177 publications on H. pylori and nanomaterials from 2003 to 2023. The study revealed a consistent increase in publications and citations. China leads in the number of publications, citation frequency, and maintains close relations with other countries. The International Journal of Biological Macromolecules and Biomaterials are the leading journals. Yu-hsin Lin is the most contributory scholar. Recent years have seen the special nanoparticles and targeted drug delivery remain a burgeoning research area.ConclusionWe conducted a bibliometric analysis of H. pylori-related nanomaterials research and identified the current research direction and frontier in the application of nanomaterials for H. pylori.